The Role of Islamic Religious Education Teachers in Forming the Morals of Students at SMK Indonesia Membangun 2 Medan - Maya Santika; Hasan Basri (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The low implementation of moral values ​​among students at SMK Indonesia Membangun 2 Medan, can be seen from the behavior of lack of discipline, low responsibility, and disrespect towards teachers and peers. This condition is exacerbated by the negative influence of the environment outside the school, such as free association and uncontrolled use of social media. Therefore, this study aims to analyze the role of Islamic Religious Education teachers in forming morals of students at SMK Indonesia Membangun 2 Medan. The research method used is qualitative descriptive with a phenomenological approach. Data collection techniques use observation, interviews, and documentation. Data analysis techniques through the stages: data condensation, data presentation, and drawing conclusions and verification. The results of the study indicate that Islamic Religious Education teachers at SMK Indonesia Membangun 2 Medan play an active role as educators, moral educators, and role models who guide students through various strategies, such as role models, habituation of worship, personal approaches, and strengthening Islamic values ​​in students' daily lives. Teachers also face various challenges, such as lack of parental involvement and factors in students' social environment. Meanwhile, teachers' efforts in forming akhlakul karimah remain significant in influencing students' positive attitudes and behaviors.